Physically and Geometrically Nonlinear Analysis of Structures Using One- and Two-Dimensional Finite Elements - Dems, K.; Kleiber, M. (Engineering Transactions, 1976)
The paper deals with the application of the finite element method for large elasto-plastic deformation analysis. The fundamental system of equations in Eulerian description has been obtained from the very general variational theorem. The geometric stiffness matrices have been derived for geometric nonlinear, one- and two-dimensional problems. The computer program, which have been based on the ASKA program package, has also been discussed. The paper is illustrated by the numerical examples.